PECULIARITIES OF THE COURSE OF PREGNANCY AND DELIVERY IN WOMEN WITH IN VITRO FERTILIZATION AT HIGH RISK OF PRETERM BIRTH - Ya.V. Shymanska (Проблеми екології та медицини)
The article is a part of the research project at the Department of Obstetrics and Gynecology No.2 of Higher Education Institution Poltava State Medical University "The role of chronic infection of the uterus and lower genital tract in the formation of obstetric and gynecological pathology" (state registration No. 0117U005276, implementation period 2017-2022). In modern reproductive medicine, infertility in marriage is considered a problem of particular importance. That is why modern assisted reproductive technologies are chosen as a method of treatment for many married couples, and their increased application necessitates intensive monitoring of the course of pregnancy and delivery. Pregnant women after in vitro fertilization programs are at high risk of miscarriage and preterm birth. The aim of the research was to study the features of pregnancy, childbirth and the condition of newborns in women after in vitro fertilization, which are classified as high risk for preterm birth. Women were included in the study at 18-20 weeks 6 days of pregnancy. We examined 85 women who became pregnant after in vitro fertilization (study group A: 37 pregnant women who refused preventive treatment and received medications in accordance with regulations; study group B: 48 pregnant women who have received the proposed treatment since their inclusion in the study. The control group included 20 apparently healthy pregnant women with its natural pregnancy onset. In pregnant women of study group A, pregnancies ended in premature birth by 1.7 times more often, and most of them occurred before 34 weeks; during pregnancy, there was a greater risk of preterm birth, which required enhanced correction in addition to conservative measures: suturing the cervix and the use of obstetric unloading pessary; the frequency of delivery by cesarean section prevailed by 1.3 times. Moreover, only in this group, pathological bleeding was observed, surgery was performed and perinatal mortality was recorded. Pregnant women who agreed to preventive treatment developed fewer preterm births after 34 weeks. Complications of pregnancy and childbirth were much less common in these women. Surgical intervention in childbirth and the frequency of delivery by cesarean section were also much less common.